Effect of application of exogenous nitric oxide at different critical growth stages in alleviating Fe deficiency chlorosis of peanut growing in calcareous soil. (21st April 2018) - Dong, Yuanjie; Chen, Weifeng; Zhuge, Yuping; Song, Yiling; Hu, Guoqing; Wan, Yongshan; Liu, Fengzhen; Li, Xuhua
ABSTRACT: This study was to investigate peanut response to application of nitric oxide (NO) at different growth stages and the effects of NO application on peanut yield and quality in calcareous soil. Sodium nitroprusside (SNP, a NO donor) solution was poured into calcareous soil at sowing, seedling, flowering, and podding stages, respectively, or at each aforesaid critical stage. Results showed that NO application increased the content of active Fe and leaf chlorophyll, which improved the photosynthesis of peanut; enhanced the ability of resistance to oxidative stress by decreased the accumulation of O2 −, H2 O2, and MDA and increased the activity of antioxidant enzymes. Nitric oxide increased the content of soil available Fe and root FCR activity, which can promote peanut absorb more Fe from the calcareous soil. What's more, peanut plants may pump a large amount of H + from root cell membrane to consume in neutralization of HCO3 −, and decrease the pH in apoplast, cytoplasm, and xylem, finally balance the mineral elements (Fe, Ca, Mg, Zn, and Cu) uptake and distribution. These results indicated that NO could improve peanut growth and development, increase peanut yield and quality. Furthermore, the application of NO at sowing or seedling stage did the most obvious effect on alleviating chlorosis of peanut in calcareous soil.